Gelagat perbelanjaan perkahwinan masyarakat Melayu Muslim menurut perspektif syariah / Syh Noorul Madihah Syed Husin - Syh Noorul Madihah, Syed Husin (2017)
The wedding scenario nowadays depicts an increase in the expenditure required for a wedding preparation. Those wishing to marry need to provide a sum of money to satisfy a variety of spending elements in ensuring the success of a wedding ceremony that meets both the Malay custom as well as the current trend. As a result, some of the youngsters today are already entrapped with debt issue for the purpose of marriage, involved in promiscuity and in some cases, it leads to the issue of late marriages. Based on this reality, it is quite interesting to see what are the actual elements spent by the Malay Muslim community today? Are the elements spent for the wedding and the spending pattern itself is recommended in Islam? Therefore, this study aimed at discussing the elements of the wedding expenses inherent in Islamic marriage procedures and analyzing the spending elements of the Malay wedding custom. The study also examines the parameter of a wedding expense as recommended in Islam. In addition, the study will also examine and evaluate the pattern of Malay Muslim wedding expenses from the Islamic perspective. For that purpose, methods of documentation, observation and interviews are employed in the data collection process. A total of 8 weddings involved in the observation and a total of 30 Malay Muslim couples who were selected through purposive sampling procedure and served as key informants were interviewed for the study. Additionally, a total of 3 experts in the field of Islamic jurisprudence and 2 wedding consultants are also served as informants. The analysis is carried out through ATLAS.ti software version 7.5.6, which involved transcription process, data preparation, coding, categorization and identification. Overall, the study found that the spending elements in Islamic marriage procedure are only focused on the dower (mahr), the wedding feast (walimah) and the preparation to celebrate the married couple. On the other hand, there are various forms of the spending elements in Malay wedding tradition that aims to meet both the Sharia-compliant practices and the non-compliant practices. The study found that there are six parameters of wedding expenses that are recommended by Islam. In addition, the study also proved that out of the four informants’ spending sources, three of the sources are encouraged in Islam. From the aspect of the elements spent by the informants, the study found that most of the elements are not supported by any Islamic legal excerpt. Nevertheless, the elements spent aims to meet the practices that are Sharia-compliant. From the view of the spending patterns of the informants, this study found some positive values in the expenses that apply the spending parameters recommended by Islam. However, there are also informants who spent contrary to what is encouraged in Islam whereby it was not in line with the concept of usefulness, moderation and affordability.